2019
DOI: 10.5004/dwt.2019.24087
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride removal from synthetic groundwater by electrocoagulation process: parametric and energy evaluation

Abstract: This study investigates the effect of several parameters on the electrocoagulation process has been studied in order to optimize the evolution of the fluoride removal percentage and the energy consumption. Optimum experimental conditions of fluoride removal were determined as: pH i = 6, J = 0.27 mA/cm 2 , t EC = 30 min, [NaCl] = 0.5 g/L, d i = 1 cm, S/V = 7.2 m-1 and Stirring speed = 300 rpm with two aluminum electrodes. These operating conditions are allowed to achieve fluoride removal of over 85% in a relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…where k 2 is the pseudo-first-order reaction rate constant. The data obtained for the adsorption of fluoride ions onto aluminium hydroxide flocs generated in the EC process satisfactorily agree with both the pseudo-first-order kinetics [41,69] and the pseudo second-order kinetics [44,58,61]. The defluoridation rates derived from the pseudo-order kinetics are dependent on the reaction conditions.…”
Section: Adsorption Kineticssupporting
confidence: 68%
See 2 more Smart Citations
“…where k 2 is the pseudo-first-order reaction rate constant. The data obtained for the adsorption of fluoride ions onto aluminium hydroxide flocs generated in the EC process satisfactorily agree with both the pseudo-first-order kinetics [41,69] and the pseudo second-order kinetics [44,58,61]. The defluoridation rates derived from the pseudo-order kinetics are dependent on the reaction conditions.…”
Section: Adsorption Kineticssupporting
confidence: 68%
“…It is worth mentioning that adsorption taking place substitution of hydroxide groups present in Al n (OH) 3n flocs by the fluoride ions is the most prevalent fluoride removal mechanism for the EC using aluminium anodes [36,41,42,44,[46][47][48][50][51][52][53]55,56,[60][61][62][63][64][65][66][67]. Coprecipitation of fluoride and hydroxide ions with aluminium ions to produce a precipitate, Al n F m (OH) 3n−m is another mechanism occurring together with the adso-rption [36,42,44,[46][47][48]50,53,55,56,68].…”
Section: Fluoride Removal Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…e results of a study revealed that electrodialysis technique could remove 50-60% of fluoride within 6 min [35]. One study showed that the fluoride removal efficiency of electrodialysis was from 50% to 90% [36]. Another study claimed that the removal rate of fluoride from drinking water by electrodialysis method was 92% [37].…”
Section: Dialysis and Electrodialysismentioning
confidence: 99%
“…In a study by Missaoui on EC treatment for fluoride removal from brackish water, the removal efficiency up to 52% was achieved under optimal status [67]. e study by Chibania et al reported the fluoride removal of over 85% in 20 min using EC technique [36]. One study indicated that electrochemical technique for defluoridation has shown a good yield for the removal of fluoride and aluminum concurrently using aluminum electrodes under 230 V DC [68].…”
Section: Electrocoagulation (Ec)mentioning
confidence: 99%